Implementasi Peraturan Menteri Agama RI Nomor 11 Tahun 2007 Tentang Pencatatan Nikah - Lisriani Utami; Ratna Farida; Anwar Abdullah (Sekolah Tinggi Ilmu Administrasi Nasional, 2019)
This is a case study at the Office of Religious Affairs (KUA) in North Aceh District. The research is expected to obtain valid information regarding the implementation of the Regulation of the Minister of Religion of the Republic of Indonesia Number 11 of 2007 concerning Marriage Registration and obstacles or obstacles in its implementation. Besides, it aims to understand and observe closely the process of implementing this regulation so that the marriage service process can be carried out in accordance with the contents of the PMA (Regulation of the Minister of Religion). The descriptive qualitative method was employed in collecting the data in this study. The results revealed that the registration of marriages had adopted the regulations stipulated in PMA No. 11 of 2007, although there were still deficiencies and obstacles in the field, both internal and external problems. However, all obstacles and challenges can still be overcome and controlled, so that the implementation of PMA No. 11 of 2007 can still be carried out even though it is not as perfect as expected.